O que é que o Bahia tem? Não é só futebol: ações de comunicação entre clube e torcedores - estudo de campanhas de Comunicação desenvolvidas pelo Esporte Clube Bahia em 2019 - Carvalho, Natália da Silva (Universidade do Vale do Rio dos Sinos, 2022)
This research in Communication analyses the communicational campaigns of Esporte Clube Bahia, which have a social background, in the context of studies on society and mediatization. In this study we approach the intersections that occur between communication, soccer and society. We seek to understand the relationships that take place between Esporte Clube Bahia and its collectives, permeating sport and the social, through strategic mediatization ways once the sports institution acts in society in an intra and extra-field way. This dissertation is built upon three main parts: in the first, we discuss how mediatization has transformed sport in society. The second part focuses on Esporte Clube Bahia going beyond the four lines of the field, first bringing conceptual aspects that reveal that the Bahian tricolor has not always been democratic. We demonstrate empirical dimensions of the research through a field study in the third part of the paper. Our study focused on two campaigns conducted by the club during the second half of 2019: SOS Praia (which deals with environmental issues) and Dedo na Ferida (which deals with structural racism) and followed their progress on Twitter. Based on the analysis, Esporte Clube Bahia brings important social debates to society, but its interactions take place in a complex, disorderly, and diffuse manner on social media.
Keywords: Comunicação; Caso midiatizado; Futebol; Coletivos; Esporte Clube Bahia; Communication; Mediatized case; Soccer; Collectives; ACCNPQ::Ciências Sociais Aplicadas::Comunicação